2015
DOI: 10.1212/wnl.0000000000001940
|View full text |Cite
|
Sign up to set email alerts
|

New-onset refractory status epilepticus

Abstract: Autoimmune encephalitis is the most commonly identified cause of new-onset refractory status epilepticus, but half remain cryptogenic. Outcome at discharge is poor but improves during follow-up. Epilepsy develops in most cases. The role of anesthetics and immune therapies warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
321
3
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(358 citation statements)
references
References 31 publications
(43 reference statements)
19
321
3
15
Order By: Relevance
“…More remote seems the possibility of drug intoxication for the presented patients: no one had a history of drug abuse or psychiatric comorbidities; no one had possible exposure to possible environmental toxic substances. Given that, we agree with previous literature that as for the actual knowledge (and its limits) it is advisable to rapidly treat these patients with immune modulatory agents, beyond just the standard treatment of SE (7, 911). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…More remote seems the possibility of drug intoxication for the presented patients: no one had a history of drug abuse or psychiatric comorbidities; no one had possible exposure to possible environmental toxic substances. Given that, we agree with previous literature that as for the actual knowledge (and its limits) it is advisable to rapidly treat these patients with immune modulatory agents, beyond just the standard treatment of SE (7, 911). …”
Section: Discussionsupporting
confidence: 89%
“…New-onset RSE (NORSE) is a rare but challenging condition, characterized by the occurrence of a prolonged period of refractory seizures with no identifiable cause in otherwise healthy individuals (4–6). Gaspard et al (7) reported a large retrospective case-series of 130 NORSE cases evaluated between 2008 and 2013. In some patients, an autoimmune or paraneoplastic etiology was identified but more than half of the cases remained cryptogenic.…”
Section: Introductionmentioning
confidence: 99%
“…[25*] Autoantibodies targeting this and other neuronal antigens have been infrequently identified in adults or children with chronic epilepsy (0–9%) or status epilepticus (< 3%), [2631,32*,33] and were found at higher frequency (15–37%) when the seizures were refractory to antiepileptic treatment. [34,35] However, with the exception of glutamic acid decarboxylase 65(GAD65) antibodies, the significance of antibodies in chronic epilepsy is unclear because they are usually identified only in serum and may disappear over time despite seizure recurrence. [31] Careful consideration should be given to the interpretation of antibodies against proteins interacting with voltage-gated potassium channels (VGKC complex).…”
Section: Introductionmentioning
confidence: 99%
“…[140] A multicenter study on patients with NORSE for whom the underlying etiology could not be determined during the first 48 hours of presentation, found that in 40% the cause was autoimmune and in the other 60% the cause remained unknown. [34] In recent reports, the use of immunotherapy improved the outcome of 42–75% of patients with NORSE but approximately 30% developed chronic epilepsy. [141,142]…”
Section: Introductionmentioning
confidence: 99%
“…N ew-onset refractory status epilepticus (NORSE) is a clinical condition characterized by prolonged pharmacoresistant seizures in an individual without active epilepsy or other pre-existing relevant neurologic disorders. 1,2 Other terms such as acute encephalitis with refractory, repetitive partial seizures; devastating epileptic encephalopathy in school-aged children; and febrile infection-related epilepsy syndrome describe the same disease entity. Although the absence of a clear acute or active toxic, metabolic, or structural cause is necessary for the diagnosis, the neuropathology of NORSE includes patients with viral infections (such as herpes simplex virus 1) and autoimmune syndromes such as autoimmune limbic encephalitis (ALE).…”
mentioning
confidence: 99%